Perceived Desirability and Feasibility: Key Factors in Forming Entrepreneurial Intentions in Accounting Education - Ulfa Nurhayani; Sondang Aida Silalahi; Weny Nurwendari; Rini Herliani (Owner : Riset dan Jurnal Akuntansi, 2025)
This research, titled "Perceived Desirability and Feasibility: Key Factors in Forming Entrepreneurial Intentions in Accounting Education," explores how perceived desirability (the desire to engage in entrepreneurship) and perceived feasibility (the practicality of engaging in entrepreneurship) shape the entrepreneurial intentions of accounting students. The study aims to evaluate how these perceptions influence students' willingness to undertake entrepreneurial activities. Using structural equation modeling (SEM), the research analyzes data from 120 students in the 6th and 8th semesters of the 2020 and 2021 cohorts who have taken entrepreneurship courses. A non-random sampling technique was employed for its convenience in data collection. The findings indicate that perceived desirability significantly impacts entrepreneurial intentions, with a t-statistic value of 6.992, while perceived feasibility also shows a significant effect, with a t-statistic value of 3.552. The study aims to provide a comprehensive understanding of the factors that motivate or hinder students' entrepreneurial intentions. The insights gained are expected to enhance accounting education and promote entrepreneurship among students. By identifying the key factors influencing entrepreneurial intentions, educational institutions can better design programs and curricula that create a supportive environment for aspiring entrepreneurs. This approach can lead to more students engaging in entrepreneurial activities, ultimately contributing to growth and innovation within the field of accounting and beyond. The research underscores the importance of fostering an entrepreneurial mindset in accounting education to drive future innovation and economic development.